Sobrecarga de ferro e estresse oxidativo em pacientes submetidos a transplante de células precursoras hematopoiéticas - Naoum, Flávio Augusto (2006)
High-dose chemotherapy with hematopoietic stem-cell transplantation (HCT) is a modality of treatment that has been used for an increasing number of diseases. However, the outcome and applicability of HCT are limited by the toxicity and mortality associated with this procedure. It is presumed that iron overload and oxidative stress with free radicals production may be associated with the complications observed after HCT. Objective: Evaluate the onset and evolution of iron overload and oxidative stress at early and late phases of HCT, and correlate this events with clinical characteristics pre and post-transplant. Patients and methods: Laboratorial markers of iron overload (serum iron, transferrin saturation and ferritin) and oxidative stress (uric acid, albumin, superoxide dismutase (SOD) and metaemoglobin) were analyzed in 21 patients undergoing allogeneic or autologous HCT. The parameters were determined before HCT, on day 0, day +14 and at 6 months post-transplant, and the results were correlated with clinical antecedents, engraftment and complications observed after HCT. Results: After high-dose chemotherapy there was a marked increase in all iron overload parameters and a reduction of uric acid and albumin levels, indicating the presence of oxidative stress. Except for ferritin levels, all the parameters that were altered after conditioning regained baseline levels at 6 moths post-HCT. Previous red blood cell transfusions correlated mainly with ferritin levels. Citotoxic treatment before HCT was associated with increased basal levels of all iron parameters and reduced acid uric concentration on day +14. Suppression of hematopoiesis, accessed by engraftment markers, was associated with iron overload (increased levels of serum iron and transferrin saturation) and oxidative stress exacerbation (reduced uric acid and SOD concentrations). Within the group transplanted in remission, patients who developed grades III-IV toxicity had higher baseline levels of iron parameters. Transplant-related mortality was increased in patients with high levels of transferrin saturation on day 0. Conclusion: Iron overload and oxidative stress are acute complications observed after high-dose chemotherapy for HCT that are probably related to delayed hematological recovery and increased morbi-mortality post-transplant. It is suggested that this parameters may be used as markers of engraftment and toxicity after HCT.